A numerical study on the fluid flow and heat transfer from a horizontal circular cylinder under mixed convection. (March 2019) - Salimipour, E.
Highlights: Flow and heat transfer from a circular cylinder under mixed convection was studied. Unsteady Navier-Stokes equations were numerically solved by a pressure-based method. A critical Grashof number was exists for suppression of the vortex shedding. A new instability mode in the flow was observed for different isothermal surfaces. Abstract: In this paper, mixed convection effects on the flow and heat transfer characteristics of a horizontal circular cylinder exposed to a laminar, incompressible, and vertical stream were numerically investigated. The vortex shedding elimination is one of the approaches for reducing the undesirable vibrations of bodies. In this regard, in the current study, using the buoyancy-aided flow, a situation was provided to eliminate the vortex shedding of the cylinder with the lowest possible drag coefficient. To reduce the thermal energy consumption and prevent the increase in the drag coefficient due to the buoyancy effect, a part of the cylinder surface was assumed to have a constant temperature, and the other part was insulated. The effect of the Grashof number and isothermal surface on the flow pattern, drag coefficient, and Nusselt number was studied at a constant Reynolds number of 200 and a Prandtl number of 0.71. To simulate the fluid flow and heat transfer numerically, the unsteady Navier-Stokes equations were solved using a finite-volume pressure–velocity coupling method with the second-order accuracy in time and space. In order to validate the present solver, some results were compared with numerical and experimental results and a good agreement was obtained. The results obtained from this study showed that for a fully isothermal cylinder, a critical value for the Grashof number existed. Consequently, for the larger values, the vortex shedding was stopped. Furthermore, by investigating the flow patterns around the cylinder, a new mode of periodic instability in a flow field was observed for a range of the Grashof numbers and isothermal surfaces. The flow in this new mode oscillated with the very low frequency. Finally, it was revealed that the use of a Grashof number of 2 × 10 4 and isothermal surface angle of 60° led to the elimination of the vortex shedding with lowest drag coefficient and energy consumption.